Challenges and considerations on the new labor market in the media industry - Álvarez Monzoncillo, José María; Suárez Bilbao, Fernando; de Haro, Guillermo (EPI SCP, 2016)
Recent changes in the economic, social, and technological environment have impacted the careers of information professionals. On one hand, new jobs and opportunities have appeared, and on the other hand, layoffs in mainstream media companies indicate that the net impact has been negative. This article attempts to analyze the most important changes in the media environment, the main forces affecting supply and demand, and the impact of changes on the careers of information professionals. Finally, we propose that some of the new radical paradigms in the world of information professionals are not conceptually new.
Keywords: Economy